2008
DOI: 10.1179/102453308x316022
|View full text |Cite
|
Sign up to set email alerts
|

Second malignancies in essential thrombocythemia (ET): a retrospective analysis of 331 patients with long-term follow-up from a single institution

Abstract: Essential thrombocythemia (ET) is a myeloproliferative disorder characterized by an indolent clinical course, with a median survival exceeding 20 years. A minority of patients undergo thrombohemorrhagic complications, which might be prevented by cytoreductive treatment in high risk categories. Alkylating agents (ALK) have been demonstrated to increase the risk of acute leukemia and myelodysplastic syndromes in patients with myeloproliferative disorders, whereas the potential oncogenicity of hydroxyurea (HU) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 21 publications
2
43
0
1
Order By: Relevance
“…[13] . Another retrospective study from Italy (n = 331) showed cumulative incidence of SPM of 13% from the time of diagnosis of ET [17] . The study determined a particularly higher incidence of AML [17] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[13] . Another retrospective study from Italy (n = 331) showed cumulative incidence of SPM of 13% from the time of diagnosis of ET [17] . The study determined a particularly higher incidence of AML [17] .…”
Section: Discussionmentioning
confidence: 99%
“…Another retrospective study from Italy (n = 331) showed cumulative incidence of SPM of 13% from the time of diagnosis of ET [17] . The study determined a particularly higher incidence of AML [17] . The risk of developing AML in ET depends on multiple factors such as old age, decreased hemoglobin and increased platelet count ≥ 1000 × 10 9 /L [28] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Drugs previously used widely for the treatment of CMPNs (eg, busulfan, P32, and chlorambucil) have well-established carcinogenic potential, [15][16][17] especially when used in combination or sequentially. 18,19 Because the increased incidence and risk of AML among CMPN patients treated with these drugs has been recognized, their use has declined. In the past several years, the most widely prescribed drug to treat patients with CMPNs has been hydroxyurea (HU).…”
Section: Discussionmentioning
confidence: 99%
“…The risk of leukemia attributed to HU when used as a single cytotoxic drug treatment for CMPN is under discussion, because studies conducted thus far have been unable to distinguish the leukemogenic effects of the CMPN disease from those of the treatment. 15,17,18 Previously, the incidence of solid tumors among CMPN patients compared with the general population was examined according to specific treatment. In a secondary analysis of a randomized controlled trial, 461 PV patients 65 years of age or more were initially treated with P32.…”
Section: Discussionmentioning
confidence: 99%